The Labouring Undead: Zombification as a Metaphor of Contemporary Crisis-Management - Chris Reitz (Law Text Culture, 2022)
The discursive field of economics is traversed by a multiplicity of metaphors. Yet, some conceptual domains lend themselves more readily to the expression of the ideological premises of financial affairs. The period since the economic meltdown of 2007 has been defined, in this regard, by a generalized apocalyptic vocabulary. In this paper, I propose to focus on the image of zombification that has become ubiquitous in crisis-management discourses, especially in the talk of so-called ‘zombie companies,’ ‘zombie banks’, or ‘zombie economies’. This discourse articulates the prospect of widespread economic collapse due to collateralized corporate debt. Inscribed with a distinct ontology of undeath, the metaphor, then, is conductive to a specific ‘necro-economic’ gesture that naturalizes the ‘Market’ as the basis of life itself, which, however, from time to time demands sacrifices to be restored and support life again. This becomes especially clear in contemporary re-circulations of Joseph Schumpeter’s theory of ‘creative destruction’, which assert that the ‘zombies’ must be neutralized to avoid the contamination of an otherwise ‘healthy’ system. As such, though, the discourse of economic zombiism is thoroughly underpinned by an imperialist unconscious that can be traced back to the emergence of the zombie figure in the context of pre-revolutionary Haiti. I propose to read the appropriation of the ‘zombie’ by neoliberal parlance as a metaphor that capital survives by. Functioning as a form of applied horror fiction, it establishes agency for ‘impersonal’ market mechanisms that externalize economic costs onto the peripheries of capitalism. In this sense, however, I argue that the rhetoric of crisis-management merely offers an imaginary resolution to a problematic that generates zombies not as an aberration but as a matter of course. Thus, I suggest that the ‘financial zombie’ functions simultaneously as a metaphor of chronic crisis and a metaphor of systemic immunization.